보건지소 환자중심 상담관리 6개월 프로그램에 참여한 당뇨병 환자의 인식 및 행동변화에 관한 연구 - 김정민(Jung Min Kim); 이혜진(HeyJean Lee); 문지영(Ji Young Moon); 조은희(Eun-Hee Cho); 백연희(Yeonheui Baeg); 최단비(Danbi Choi); 이지혜(Jihye Lee); 권혁녀(Hyeoknyeo Gwon) (보건교육건강증진학회지, 2017)
Objectives: Health coaching became effective tool for management of chronic diseases. This study was designed to investigate the effects of coaching program on comprehensive lifestyles modification with Type 2 Diabetes Mellitus(T2DM) patients. Methods: The study investigated using pre- & post-test. Diabetes health coaching program was taken at branches of community health center for 6 months. This program was consisted of monthly face to face counseling and weekly telephone counseling. At enrollment and after 6 months, we performed a questionnaire survey consisted of the diabetes knowledge, practice of disease management (diet, blood sugar testing, and foot care), self-efficacy, subjective health status, health behavior (smoking, alcohol consumption, and physical activity). Also we checked blood pressure, body mass index, fasting serum glucose, postprandial glucose, total cholesterol, and glycosylated hemoglobin. Results: We analyzed 6-month follow-up data from 54 patients. They showed significant improvements in diabetes knowledge, disease management of foot care, self efficacy, the amount of exercise, and systolic blood pressure. Conclusions: Although this study didn’t show metabolic improvement of T2DM patients, it resulted the improvement of self efficacy, the amount of exercise, and systolic blood pressure. Using Diabetes health coaching program seems to be helpful in T2DM patients at branch of community health center. KCI Citation Count: 0